PERANCANGAN DAN PENGEMBANGAN MESIN PENGAHANCUR SAMPAH ORGANIK MODEL PISAU PUTAR (ROTARY) - Yuni Hermawan; Ririn Endah Badriani; M Sakharuddin (ROTOR, 2012)
This design to make the organic garbage crusher machine which its structure can be made easy and cheap by society, and can be operated simply, moved by diesel engine 20 hp own the ability can can break the permanent organic garbage upon which compost. This activity  divisible in 2 solution framework that is technical solution framework and solution non technical. Technical Approach: approach to society of orchard Damsari by attending method/machine to processes and dissociate the garbage type so that heaping sum up the deductible garbage. Approach of non technical: approach to citizen by guiding and growing to develop the society awareness about its important keep cleaning environmental and sanitasi. From final this activity inferential that: making of organic garbage crusher machine earn the especial problems faced by group society orchard of Damsari town Sempu Banyuwangi. Making of enforceable organic garbage  Machine better as according to time plan which have been determined, Especial problems partner concerning garbage processing with the this machine attendance expected depending to on duty deductible town Sempu hygiene and created  society of self manage garbage. Result from this garbage processing machine in the form  organic garbage upon which compost of the size 2-3 cm and organic garbage process become the compost used by farmer group, so that indirectly can improve the earnings of society of orchard Damsari and permeating new labour. Keyword: crusher, organic garbage and compost.